An empirical study to evaluate the student competency of vocational education - Rihab Wit Daryono; Muhammad Agphin Ramadhan; Nur Kholifah; Fajar Danur Isnantyo; Muhammad Nurtanto (Institute of Advanced Engineering and Science, 2023)
The low work readiness of vocational education (VE) graduates is caused by a mismatch of competencies with job demands. The unemployment rate for VE graduates is increasing due to low competency mastery and job absorption. The purpose of this study is to determine the competency needs of architectural engineering graduates according to the current demand for the construction industry. The research sample consisted of 193 respondents consisting of VE teachers and practitioners from the construction industry in Indonesia. The Covariance-Based Structural Equation Modeling (CB-SEM) analysis is used for the evaluation of the structural models of architectural engineering competency demands. The results of the analysis test using Confirmatory Factor Analysis (CFA) show that the construct validity of the evaluation model is in a good category. The evaluation model testing met the statistical criteria of goodness of fit. The model substantially explains 89.75% of the various competencies that must be mastered by architectural engineering graduates and suitable for use in Indonesia and other countries.